PELATIHAN PENDEKATAN STEAM TERINTEGRASI TEKNOLOGI BAGI GURU TINGKAT SEKOLAH DASAR - Jeffry Handhika; Tri Candra Wulandari; Nugroho Adi Pramono; Kawakibul Kawakibul (Jurnal Terapan Abdimas, 2025)
Abstract.The purpose of this training is to improve pedagogical skills (the use of the PbL/PjBL model with the STEAM Science, Technology, Engineering, Arts and Mathematics approach) and technology integration in teacher learning. By increasing these two abilities, it is expected that the quality of learning will increase and have an impact on students' scientific literacy. The activity was carried out at one of the Madrasah Ibtidaiyah in Malang Regency. The training was designed in the form of delivering pedagogical materials, demonstrations, practices using media, and task. The potential for implementing the PbL & PjBL model with a STEAM approach integrated with technology is in the high category and received positive responses from participants based on the questionnaire. The majority of participants said that the training activities carried out were very useful. Abstrak. Tujuan dari pelatihan ini adalah meningkatkan kemampuan pedagogik (penggunaan model PbL/PjBL dengan pendekatan Science, Technology, Engineering, Arts and Mathematics STEAM) dan integrasi teknologi dalam pembelajaran guru. Dengan meningkatnya dua kemampuan ini diharapkan kualitas pembelajaran meningkat dan berdampak pada literasi sains siswa. Kegiatan dilakukan di salah satu Madrasah Ibtidaiyah di Kabupaten Malang sejumlah 15 peserta. Pelatihan dirancang dalam bentuk penyampaian materi pedagogik, demonstrasi, praktek menggunakan media, dan penugasan. Potensi menerapkan model PbL & PjBL dengan pedekatan STEAM terintegrasi teknologi pada kategori tinggi dan mendapatkan respon positif dari peserta berdasarkan kuisioner. Mayoritas peserta menyampaikan kegiatan pelatihan yang dilakukan sangat bermanfaat.